Exploring the Chemopreventive Potential of Artemisia annua Methanolic Extract in Colorectal Cancer Induced by Azoxymethane in Mice - Faris Alrumaihi (Pharmaceuticals)
Background/Objectives: Colorectal cancer (CRC) remains a major global health burden, necessitating innovative preventive approaches. Artemisia annua (A. annua), known for its extensive pharmacological properties, has shown potential in cancer therapy. This study investigates the chemopreventive efficacy of methanolic extract of A. annua (MEA) in an azoxymethane (AOM)-induced murine model of CRC, with a focus on its antioxidant, biomarker modulation, and pro-apoptotic activities. Methods: MEA was obtained via cold solvent extraction, yielding 39%, and demonstrated potent in vitro cytotoxicity against HCT116 and RKO colon cancer cell lines, with IC50 values of 20 µg/mL and 15 µg/mL, respectively. Swiss albino mice were treated with MEA beginning two weeks before AOM induction, with treatment continuing for 21 weeks. Survival was monitored for 40 weeks. Key outcomes included serum biomarker levels (ADA, GGT, CD73, LDH), antioxidant enzyme activities (SOD, CAT, GPx1, MDA), reactive oxygen species (ROS) modulation, apoptosis induction, and histopathological evaluation. Results: MEA significantly improved survival rates, reduced AOM-induced weight loss, and modulated cancer biomarkers, with marked reductions in ADA, GGT, CD73, and LDH levels. Antioxidant defenses were restored, as evidenced by increased SOD, CAT, and GPx1 activities and decreased MDA levels. ROS levels were significantly reduced, and apoptosis in colonic cells was effectively induced. Histopathological analysis revealed substantial mitigation of CRC-associated morphological abnormalities. Conclusions: MEA exhibits robust chemopreventive properties, demonstrating its potential to reduce oxidative stress, modulate key biomarkers, and induce apoptosis in CRC. These findings position MEA as a promising natural candidate for CRC prevention and therapy, warranting further exploration for clinical application.